2021
DOI: 10.2174/1573402115666190410153634
|View full text |Cite
|
Sign up to set email alerts
|

Perivascular Adipose Tissue Oxidative Stress on the Pathophysiology of Cardiometabolic Diseases

Abstract: Most of the systemic blood vessels are surrounded by the perivascular adipose tissue (PVAT). Healthy PVAT is anticontractile and anti-inflammatory, but a dysfunctional PVAT has been suggested to link cardiometabolic risk factors to vascular dysfunction. Vascular oxidative stress is an important pathophysiological event in cardiometabolic complications of obesity, type 2 diabetes, and hypertension. PVAT-derived adipocytes generate reactive oxygen species (ROS) including superoxide anion and hydrogen peroxide th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 0 publications
0
16
1
Order By: Relevance
“…The media remained protected from the inflammatory infiltration in the samples with inflammatory infiltration of PVAT. Our findings were unexpected, as several previous studies support the view that PVAT, primarily when infiltrated with inflammatory cells, promotes the development of CAD [7,9,16]. The primary function of the media is to maintain appropriate arterial tone allowing adequate perfusion of tissues and maintaining appropriate blood pressure.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…The media remained protected from the inflammatory infiltration in the samples with inflammatory infiltration of PVAT. Our findings were unexpected, as several previous studies support the view that PVAT, primarily when infiltrated with inflammatory cells, promotes the development of CAD [7,9,16]. The primary function of the media is to maintain appropriate arterial tone allowing adequate perfusion of tissues and maintaining appropriate blood pressure.…”
Section: Discussioncontrasting
confidence: 41%
“…Both demands are achieved by the systemic sympathetic control and paracrine vasoactive factors released by the cells of the arterial wall. It has been shown that not only endothelial cells but also adipocytes from PVAT, as well as inflammatory cells, play an essential role in maintaining vascular tone and structure [6,12,[16][17][18][19]. In healthy adipose tissue, including PVAT, alternatively activated macrophages M2 prevail.…”
Section: Discussionmentioning
confidence: 99%
“…The anticontractile effect of PVAT was first described in rat thoracic aorta (Soltis and Cassis, 1991), followed by other vascular beds, including small mesenteric arteries (Aoqui et al, 2014;Gil-Ortega et al, 2014;Withers et al, 2017). It has been suggested that the presence of cardiometabolic risk factors, such as obesity, alters the secretory pattern of PVAT and might result in vascular dysfunction (Victorio and Davel, 2019). PVAT-dependent vascular dysfunction has been demonstrated in the aorta (da Costa et al, 2017;Ketonen et al, 2010) and mesenteric resistance arteries (Agabiti-Rosei et al, 2014;Gil-Ortega et al, 2014;Withers et al, 2017) in rat and mouse obese models.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al previously reported that the knockdown of Nnat expression reversed the effects of adiponectin on promoting the differentiation of 3T3-L1 cells into mature adipocytes, and inhibiting the release of inflammatory factors and oxidative stress through NF-κB signaling pathway (7). Inflammation and oxidative stress affect adipose metabolism and participate in the incidence and development of various diseases, such as AS, obesity, hypertension, and diabetes (18)(19)(20)(21). Analysis of clinical EAT samples in this study showed that the expression of Nnat protein in EAT of CAHD patients was significantly down-regulated compared that in EAT of non-CAHD patients.…”
Section: Discussionmentioning
confidence: 99%